Experimental research of thermographic control for detection of cracks in steel structures - Kolesnichenko, S.; Popadenko, A. (Ways to Improve Construction Efficiency, 2020)
The paper presents the results of experimental research of the possibility of using thermographic non-destructive testing for the search of cracks in steel structures. The basis of non-destructive thermal control is the registration of changes in the thermal field that occurs in the case of disturbance of the thermodynamic equilibrium of object with an environment that appears on the surface, and parameters of which allows to obtain the necessary information. The thermal control method is based on the interaction of the thermal field of object with thermodynamically sensitive elements (thermocouple, photodetector, liquid crystal element, bolometer) that convert the field parameters (intensity, temperature gradient, contrast, variability) into the electrical signal of the recording device. An experiment is described which proves the possibility of using thermal nondestructive testing for the detection of cracks in steel structures. As measuring instruments for the experiment were used thermal imagers with different resolution of the matrix of the IR image (thermal image), infrared thermohygrometer, luxmeter. The problems encountered during the use of thermal non-destructive testing and possible solutions are indicated. The authors conclude that the thermographic control method can be used in the examination of steel structures for the qualitative assessment of cracks.